Analysis of Teacher Assessment on the Effectiveness Of Problem-Based Learning in Improving Student Learning Outcomes at MA Putri Al-Ishlahuddin Kediri Lombok Barat - Lalu Pradipta Jaya Bahari; Nurjannah Nurjannah; Akhmad Asyari (Universitas Islam Negeri (UIN) Mataram, 2022)
Physics is a subject that has a relatively small number of enthusiasts—caused by the factors that influence student achievement in learning physics, which are considered less attractive or do not significantly impact learning outcomes. This study aimed to determine the effectiveness of the Problem-Based Learning (PBL) learning model on student performance in improving psychomotor aspects and student learning outcomes in physics lessons. The method used in this research is descriptive quantitative with the sampling technique using simple random sampling. The data collection technique uses a questionnaire filled out by the teacher during teaching and learning activities in class. The results showed that based on the theory put forward by Arikunto, the resulting percentage value was 90.4% with a good predicate based on its effectiveness in improving student performance in learning. The conclusion from this research is the high level of student performance in the learning process. Because students are required to always be active in working together to solve and make solutions to problems set by the teacher, this research is considered suitable and recommended to be applied to further studies that have constraints on students' performance and learning outcomes.